Weed management in rice using crop competition-a review. (May 2017) - Dass, Anchal; Shekhawat, Kapila; Choudhary, Anil Kumar; Sepat, Seema; Rathore, Sanjay Singh; Mahajan, Gulshan; Chauhan, Bhagirath Singh
Abstract: Rice is the principal food commodity for millions of people. Its growing demand invokes for an enhanced productivity, but with limited land and water resources. Among various biotic stresses limiting rice yields, the major stress is imposed by weeds, particularly in direct-seeded rice (DSR) under aerobic situations. In weedy situations, the yield losses may ascend to 50–60% in puddled transplanted rice and 70–80% in DSR. Herbicidal weed management is the most widely adapted strategy, however, the large scale application of herbicides mainly of same or similar mode of action is constrained by the risks of environmental trade-offs, introduction of herbicide-resistance in different bio-types of weeds, non-selectivity and narrow-spectrum of herbicides. Hence, ecological approaches, like weed-competitive cultivars, alterations in seed rates, and planting patterns could be highly useful in reducing the weed menace. This review reveals that main characteristics imparting weed-competitiveness to rice include selection of cultivars, seedling vigour, early and faster establishment of seedlings, root-shoot characteristics, and self-supportive allelopathy. In DSR, a higher seeding rate of 50–60 kg ha −1 has been found to reduce weed biomass by ∼50%, without imposing any yield penalty and, thus desirable under weedy conditions. Similarly, a narrow row spacing of 15–25 cm in DSR and 20 × 10 cm in puddled transplanted rice resulted in higher productivity with minimum weed infestations. Although all such practices are not sufficient enough to suppress weeds completely, they are useful in reducing the herbicide dose up to 50% on 158 m ha area under rice cultivation in the world, thereby, reducing huge environmental trade-offs. Highlights: Weeds cause 70–80 losses in direct seeded rice and use of herbicides is constrained by many risks. Use of weed-competitive cultivars reduces weed menace considerably. A higher seed rate of 50–60 kg ha −1 reduce weed biomass by about 50%. A narrow row spacing of 15–25 cm reduce weed problem and increase rice yield. Employing crop-competition can cut herbicide dose by about 50% in direct seeded rice.